The practice of physical activity on life history of people with physical disabilities - Lehnhard, Greice Rosso (2012)
This study have had the aim to analyze the physical activity practice in different life periods for people with disabilities. In the project there were involved nine young male adults, carrying some physical disability and who practiced physical activities and/or sports. To collect the data it was used an interview composed of some questions concerning to life history, disability and physical activities in different life stages, the analysis of data was by categories. During childhood and adolescence eight participants practiced dynamic activities and joined Physical Education  classes; as adults four continued previous practices , one has started and another has no access; nowadays they practice many sports and six believed that physical disability interfers with sports practicing. And yet, seven assumed that activities during school age interfere in which they practice at the moment, emphasizing the importance of people with physical disability joining Physical Education classes.